Understanding the growing gender awareness of living under patriarchy in Kate Chopin’s “The Awakening” - Córdova Guerra, Romina (Universidad de Santiago de Chile, 2021)
Integrantes: Romina Córdova, Sofía Cornejos, Karina Donoso, Valentina Lobos
Keywords: Chopin, Kate, 1851-1909. The Awakening; Identidad de género en literatura; Feminismo en literatura